Potential for utilizing Socioeconomic Registration Data to improve targeting of Ministry of Manpower’s Training and Business Assistance Program - Raisa Putra, Riski (Bappenas Working Papers, 2024)
This policy paper explores the potential for utilizing Registrasi Sosial Ekonom (Regsosek - Socioeconomic Data Registration) to improve the targeting of training and business assistance programs managed by Kementerian Ketenagakerjaan (Kemnaker – Ministry of Manpower) in Indonesia. Indonesia’s National Long-Term Development Plan (RPJPN 2005-2025) aims to create a developed, self-reliant, just, and democratic society. The paper identifies key issues in the implementation of Kemnaker's programs, including Tenaga Kerja Mandiri (TKM - Self-Employed Workers Program) and Pelatihan Berbasis Kompetensi (PBK - Competency Based Training). These issues include inaccurate targeting, lack of inclusivity, and disparities in the geographical distribution of beneficiaries. Data from Regsosek reveals critical gaps in program participation, business ownership, and inclusivity, particularly for marginalized groups such as people with disabilities and women. Moreover, there are significant disparities in program access, with a higher concentration of benefits accruing to wealthier individuals, indicating the need for more effective targeting mechanisms.By leveraging the comprehensive socioeconomic data provided by Regsosek, Kemnaker can develop targeted solutions that more effectively address the unique needs of different demographic groups, ensure equitable resource allocation, and ultimately improve the overall impact of its training and business assistance programs. The paper underlines the importance of data-driven policies in achieving sustainable economic growth and social equity. It points to the critical role of accurate data in informed decision-making, efficient resource allocation, and continuous program improvement. The integration of Regsosek data is presented as a core strategy for enhancing the precision and effectiveness of government interventions aimed at fostering economic independence and improving the livelihoods of Indonesia’s diverse population. By addressing these challenges and implementing the recommended strategies, Indonesia can move closer to its vision of a prosperous, equitable, and inclusive society.